CO line ratios in molecular clouds: the impact of environment - Peñaloza, Camilo H.; Clark, Paul C.; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. Line emission is strongly dependent on the local environmental conditions in which the emitting tracers reside. In this work, we focus on modelling t
Advance access publication 2017 December 20
Gesehen am 07.02.2020